Konstruksi Penalaran Hakim dalam Menetapkan Pelaku Materiil Tindak Pidana Pembunuhan Berencana sebagai Justice Collaborator (Analisis Kasus ER pada Putusan Nomor 798/Pid.B/2022/PN JKT.SEL) - Nofal, La Ode (Lembaga Intelektual Muda Maluku, 2024)
This research is based on the existence of premeditated murder incidents committed by several criminals in the context of the inclusion of criminal acts (delneming). One of the perpetrators of the crime, namely the Defendant ER, was considered by the judge to be a person who participated in the crime of premeditated murder, so the judge in his decision Number 798/Pid.B/2022/Pn Jkt.Sel designated the Defendant as a justice collaborator. The type of research used in is normative juridical research. Library research techniques are using primary legal materials such as basic norms, laws and regulations, and court decisions, secondary legal materials, namely magazines, books, or newspapers, and tertiary legal materials, namely dictionaries, articles, or reference materials. The data analysis technique used is the normative-qualitative analysis method. The results of the data analysis show that the legal construction of the determination of the perpetrator of crime as a justice collaborator can be interpreted in four elements, namely problematic scope, should be interpreted as not just organized crime but all criminal acts that have a maximum threat of eight years in prison, and with the note that before the determination of the perpetrator as a Justice Collaborator, the principle of subsidiarity is first applied. where the granting of the status of a Justice Collaborator can only be done as a substitute if other means of exposing the crime have failed